(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
The article examines the features of teaching the Chinese language to primary school students. It is proved that in the first month of study, learning Chinese for two hours a week, a student can fully master no more than 5-6 hieroglyphs.